Sindhi in Malaysia-Language maintenance or language shift? - Maya Khemlani David (Journal of Modern Languages)
This article will discuss whether the Sindhi community of Malaysia is experiencing language shift or maintaining the use of the ancestral language, Sindhi. The traditional questionnaire methodology based on the domain construct (cf. Fishman, 1964) was used to analyze whether the ethnic language is maintained. The results of the questionnaire approach to data collection are by themselves insufficient to present a comprehensive picture of the process of shift. Consequently, the data used in this study comprises a three-year ethnographic study of the community's choice of language choice in homes and in intracommunity encounters.